Red blood cell profile in patients with mild, moderate and severe COVID-19 (IMC Journal of Medical Science, 2021)
Background and objectives: Coronavirus disease 2019 (COVID-19) pandemic has affected millions of people world-wide. It is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Increasing evidence has shown abnormalities of different hematological parameters with the severity of the diseases. The present study was undertaken to determine the red blood cell (RBC) profile in different categories of COVID-19 patients.Materials and methods: The study was conducted from January 2020 to December 2020. Reverse transcriptase-polymerase chain reaction (RT-PCR) positive COVID-19 patients were enrolled. Patients were categorized into mild, moderate and severe COVID-19 cases. Blood samples were analyzed by Automated Hematology Analyzer for hemoglobin concentration, total erythrocyte count and RBC indices. ANOVA followed by Bonferroni test, Chi square test, Spearman’s rho correlation coefficient test were performed as applicable using SPSS version 25.0.Results: A total of 100 RT-PCR positive COVID-19 patients were included in the study. There were 25, 38 and 37 mild, moderate and severe cases respectively. The mean age of the study participants was 44.68 + 13.16 years (range: 18 to 65 years). There were 67 (67%) males and 33 (33%) females. No significant difference in hemoglobin (Hb), hematocrit (HCT), total RBC count, red blood cell distribution width (CDW) was observed among the three groups. Significant negative correlation of mean corpuscular volume (MCV) and mean corpuscular hemoglobin (MCH); rs-0.362 & -0.255 respectively) was observed with disease severity.Conclusion: The study showed low MCV and MCH were significantly related with the severity of the COVID-19 illness. Therefore, comprehensive analysis of the RBC profile would be helpful to understand the disease course.Ibrahim Med. Coll. J. 2021; 15(2): 26-31